Model Test Study on the Influence of Train Speed on the Dynamic Response of an X-Section Pile-Net Composite Foundation - Shanshan Xue; Yumin Chen; Hanlong Liu (Shock and Vibration)
Based on a large-scale X-section pile-net composite foundation model, we experimentally studied the dynamic characteristics of the pile-net composite foundation under a high-speed railway train load; analyzed the distribution characteristics of the dynamic stress, dynamic displacement, speed, and acceleration of the foundation soil under different train speeds; and investigated the vibration response of the track subgrade foundation system, as well as the distribution characteristics and attenuation pattern of the dynamic stress inside the subgrade foundation under cyclic train loading. The following results are obtained. The peak vertical vibration speed and the peak acceleration attenuate by 90% and 62.5%, respectively, after passing through the embankment. The vibration velocity increases linearly with the train speed; the ratio of the peak dynamic soil stresses at the top of the piles and between the piles is approximately 3.4. The change in train speed does not have a large influence on the peak dynamic displacement or peak dynamic soil stress. The peak spectral vibration acceleration caused by the train loading is located within the range of medium-to-low-frequency vibrations, and the characteristic frequency corresponds to the passing frequency of the bogies and carriages; as the train speed increases, the peak spectral vibration acceleration increases, and the high-frequency components increase significantly.